Body image in different periods of adolescence - Miranda,Valter Paulo N. (2014)
Objective: To analyze body image in different periods of adolescence.Methods: This cross-sectional study enrolled students aged ten to 19 years old of public schools in small districts of Minas Gerais, Southeast Brazil. The Body Shape Questionnaire (BSQ), the Body Dissatisfaction Assessment Scale for Teenagers and the Silhouette Scale for Teenagers (SST) were used. Adolescence phases were classified according to the subjects' ages. Weight and height were measured in order to calculate the body mass index and the nutritional status. Results were analyzed by logistic regression.Results: The study emolled 531 teenagers (318 females). The average age was 15.6±2.2 years and 84.6% were eutrophic. The prevalence of body dissatisfaction varied from 28.9% (BSQ) to 78.9% (SST). Overweight adolescents presented greater dissatisfaction (BSQ: OR 3.66, p<0.001; SST: OR 4.108, p<0.001). Dissatisfaction also occurred for females and those at the early adolescence (p<0.05).Conclusions:A low prevalence of dissatisfaction with the body image was observed among adolescents in small towns of Minas Gerais; however, most of them wished a different silhouette than the current one. The results showed that younger adolescents had higher dissatisfaction than their peers, as well as female and overweighed adolescents.